Dieta do ouriço-branco, Tripneustes ventricosus (Lamarck, 1816), no Arquipélago de Fernando de Noronha, PE - Cavalcanti, Augusto Muniz (2007)
Sea urchins are benthic macroinvertebrates that inhabit shallow coastal waters in tropical and temperate zones. Urchins are usually classified as generalists or omnivores as they can adjust their diet according to the food resources available in the environment. Due to the strong grazing pressure they may exert, urchins have an important role in marine ecosystems, occupying different trophic levels and stimulating the intensification of the dynamics of communities where they occur. In 2004, a monitoring program focused on the population dynamics of the white sea urchin, Tripneustes ventricosus, has been initiated in the Fernando de Noronha Archipelago. At the same time, a surprisingly lack of information on the species biology has been noted, despite their wide geographical distribution and economic importance in many parts of its range. Hence, this work was developed to provide information on the feeding habits of T. ventricosus in the archipelago. Ten specimens were collected between December 2006 and July 2007 at two sites of the archipelago, Air France and Sueste Bay for biometrics and analysis of gut contents. Test diameters ranged from 9.19 cm (± 1.1) to 10.08 cm (± 0.58). Calculated stomach repletion index (IRE) was higher (p <0.05) in the Air France site and also during January and July. The IRE was not correlated to the gonad index. Fifteen different species of algae were detected in a total of 120 stomachs examined: 4 Chlorophytas, 4 Phaeophytas and 6 Rhodophytas. Food diversity (p <0.05) was higher in December 2006 and January 2007. Although several items had a high frequency of occurrence, they were low represented in terms of weight, and consequently, had a low level of relative importance. The brown algae Dictyopteris spp and Dictyota spp, followed by the green algae Caulerpa verticillata accounted for the greatest importance in T. ventricosus diet, comprising about 90% of the consumed items